The need to review the Elderly Care Law - Hasan Ahamd (Tamilis Synex: Multidimensional Collaboration, 2023)
Nowadays, we are witnessing an increasing number of elderly people in the world. The World Health Organization describes this phenomenon as the greatest victory for humanity. Indonesia is one of the countries with the largest number of elderly people in the world. The World Health Organization predicts that in 2025 Indonesia will have the fifth highest proportion of elderly people in the world. This article attempts to answer: What are the latest scientific studies conducted on the elderly? What should be the maximum old age category in Indonesia? Is reviewing Law No. 13 of 1998 regarding elderly care (the Elderly Law) urgent? Finally, what is the role of the Indonesian Parliament in this issue? The researcher uses the qualitative method with a combination of interview techniques and literature studies. This article attempts to answer: What are the latest scientific studies conducted on the elderly? What should be the maximum old age category in Indonesia? Is reviewing Law No. 13 of 1998 regarding elderly care (the Elderly Law) urgent? Finally, what is the role of the Indonesian Parliament in this issue? So, if there is a reward for the elderly, the burden on productive people will be heavier. Gerontologists offer the concept of active aging as a solution. It is a concept that calls on us to look at the elderly not as burdens, but as people with economic and social potential. A comprehensive and operational solution policy supported by implementers at the central, regional and community levels would make remuneration for the elderly a blessing. Therefore, there is an urgent need to review Law No. 13 of 1998 regarding elderly care, while including several important matters, namely the principle of humanity, the rights of the elderly, collecting elderly data, and economic protection for the elderly.